Closed loop stimulation in heart failure patients with severe chronotropic incompetence: responder versus non-responders. (24th May 2021) - Proff, J; Merkely, B; Papp, R; Lenz, C; Nordbeck, P; Butter, CH; Meyerhoefer, J; Doering, M; Maccarter, DJ; Ingel, K; Thouet, TH; Roser, M
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Biotronik SE & Co. KG Woermannkehre 1 12359 Berlin Background: The prevalence of chronotropic incompetence (CI) in heart failure (HF) population is high and negatively impacts prognosis. Rate-adaptive pacing (RAP) is an important treatment option for CI. However, only a proportion of HF patients treated with cardiac resynchronisation therapy (CRT) devices benefit from accelerometer-based RAP in terms of exercise tolerance, functional capacity, and quality of life (QoL). Further research is needed to identify patient characteristics predicting positive response to RAP, and to evaluate performance of alternative sensors such as closed loop stimulation (CLS) driven by cardiac impedance measurements. An optimal outcome measure is represented by ventilatory efficiency (VE) slope during cardio-pulmonary exercise test (CPX) because of superior prognostic value. Purpose: The purpose of the BIO|Create pilot study was to assess the benefit of CLS in CRT patients with CI. In this predefined subanalysis, we identify predictors of positive response to CLS (reduction of VE slope by ≥5%) and compare study outcomes in responders vs non-responders. Methods: The study enrolled CRT patients with NYHA class II or III and severe CI (<75% of age-predicted maximum heart rate [HR] or <50% of HR reserve utilised at end-exercise). Patients were randomised to DDD-CLS mode or to DDD pacing at 40 beats/min for 1 month, followed by crossover for another month. At 1- and 2-month follow-ups, exercise tolerance was assessed by treadmill CPX, functional capacity by 6-min walk test, and QoL by the EQ-5D-5L and Minnesota Living with HF (MLHFQ) questionnaires. Results: Among 17 patients with full follow-up datasets, 8 (47%) were responders to CLS. Compared to non-responders, responders had larger left ventricular (LV) ejection fraction at baseline (46 ± 3 vs 36 ± 9 %; p = 0.0070), smaller end-diastolic (121 ± 34 vs 181 ± 41 ml; p = 0.0085) and end-systolic (65 ± 23 vs 114 ± 39 ml; p = 0.0076) LV volumes, and were predominantly in NYHA class II (p = 0.0498). For study outcomes, the mean difference between DDD-CLS and DDD-40 modes in responders vs non-responders was - 6.1 (-16.4%) vs +2.7 (+6.8%) for VE slope (both p < 0.05), +0.5 vs -0.2 ml/min (O2 uptake efficiency slope), +1.3 vs -0.3 ml/kg/min (peak O2 uptake), +1.4 vs -0.75 mmHg (end-exercise end-tidal CO2), 16 vs 7 m (6-min walk distance), 0.08 vs 0.06 (EQ-5D-5L index), 1.9 vs 0 (EQ-5D-5L scale), and -2.5 vs +1.75 (MLHFQ). Conclusions: For the first time, predictors for positive outcome of RAP in CRT patients have been identified. Patients with less advanced HF were responders to RAP driven by CLS principle. In addition, a consistent increase in exercise and functional capacity and QoL in these patients could be achieved. In contrast, patients with advanced HF experienced worse exercise capacity and QoL during RAP, suggesting caution if RAP is desirable due to CI. Further clinical research is needed to evaluate if positive response to RAP can improve hard clinical outcomes.